Energy use in paddy production: NKEA’s estate in MADA area - Baharudin, Siti ‘Aisyah; Mohamed Arshad, Fatimah (Malaysian Agricultural Research and Development Institute (MARDI), 2014)
This study was conducted to determine the energy use in the production of paddy in NKEA’s estate in Muda Agricultural Development Authority (MADA), Malaysia for season 1/2012 – 2/2012. Data were collected through questionnaires and in-depth interviews with managers of NKEA’s estate under province I in the MADA area. The calculation of energy usage is comprised of fuel energy, human energy, fertilisers, pesticides and seed. An energy analysis of paddy production in NKEA’s estate in MADA indicates that the planting practices are largely dependent on direct seeding (75%) and transplanting (15%). The energy input-output ratio is 6.28 for the direct seeding and 6.18 for transplanting. Results show that the total energy input for transplanting (19,972.37 MJ/ha) is higher than the input used in direct seeding method (19,659.21 MJ/ha). Meanwhile, the total output for paddy production is 12,3505 MJ/ha. The study indicates that among the activities involved in the direct seeding cultivation technique, fuel energy usage is highest in land preparation (38%), followed by harvesting (25%), post-harvest (15%), crop management (14%) and planting (6%). High energy input could increase the input risk in paddy production as the increase in world oil prices has a direct impact on the domestic prices of fuel and indirect effect on fertiliser prices. These findings suggest the need to decrease dependency on energy which could be done either through efficient use of energy or utilising organic input.